An online decision tree for vaccine efficacy trial design during infectious disease epidemics: The InterVax-Tool. Issue 31 (18th July 2019) - Bellan, Steven E.; Eggo, Rosalind M.; Gsell, Pierre-Stéphane; Kucharski, Adam J.; Dean, Natalie E.; Donohue, Richard; Zook, Matt; Edmunds, W. John; Odhiambo, Frank; Longini, Ira M.; Brisson, Marc; Mahon, Barbara E.; et al.
Highlights: Phase 3 vaccine efficacy trial design during outbreaks and emergencies is challenging. InterVax-Tool (vaxeval.com) is a structured decision-support tool for trial design. Optimal design must include epidemiological, statistical, ethical, and logistical difficulties. Navigating these issues in real-time requires tools to assist in decision-making. Dynamic guidance, note taking, and tailored choices are key to good user engagement. Abstract: Background: Licensed vaccines are urgently needed for emerging infectious diseases, but the nature of these epidemics causes challenges for the design of phase III trials to evaluate vaccine efficacy. Designing and executing rigorous, fast, and ethical, vaccine efficacy trials is difficult, and the decisions and limitations in the design of these trials encompass epidemiological, logistical, regulatory, statistical, and ethical dimensions. Results: Trial design decisions are complex and interrelated, but current guidance documents do not lend themselves to efficient decision-making. We created InterVax-Tool (http://vaxeval.com ), an online, interactive decision-support tool, to help diverse stakeholders navigate the decisions in the design of phase III vaccine trials. InterVax-Tool offers high-level visual and interactive assistance through a set of four decision trees, guiding users through selection of the: (1) Primary Endpoint, (2) Target Population, (3) Randomization Scheme, and, (4) Comparator. We provide guidance on how key considerations – grouped as Epidemiological, Vaccine-related, Infrastructural, or Sociocultural – inform each decision in the trial design process. Conclusions: InterVax-Tool facilitates structured, transparent, and collaborative discussion of trial design, while recording the decision-making process. Users can save and share their decisions, which is useful both for comparing proposed trial designs, and for justifying particular design choices. Here, we describe the goals and features of InterVax-Tool as well as its application to the design of a Zika vaccine efficacy trial.